#### Answer

$r_{2}=Rr_{1}\div({r_{1}-R})$

#### Work Step by Step

$R(r_{1}+r_{2})=r_{1}r_{2}$
$Rr_{1}+Rr_{2}=r_{1}r_{2}$
$Rr_{1}=r_{1}r_{2}-Rr_{2}$
$Rr_{1}=r_{2}(r_{1}-R)$
$r_{2}=Rr_{1}\div({r_{1}-R})$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$r_{2}=Rr_{1}\div({r_{1}-R})$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.